Trabalhadoras domésticas: mercado de trabalho segmentado ou integrado? - Santos, Jankiel Aparecido Lima dos (2010)
There is a plethora of essays assessing the topic of labour market segmentation, but their common strategy of appraising jointly several categories of workers has seemingly made it harder for researchers to reach a consensual view about the existence (or lack) of segmentation in the Brazilian labour market. In this essay just a lone category is chosen as the focus of analysis – namely the one comprising domestic female employees - so as to try to dim that difficulty whereas dealing with a relevant group of the Brazilian labour force, whose components represent 1/6 of total female job posts or roughly 7% of total Brazilian employees. Therefore, should one succeed in finding robust evidences that important group of workers faces a segmented market and one will not be able to state the Brazilian labour market as a whole is an integrated one. That is the conclusion that arises in this survey using two different methods (ordinary least squares and Blinder-Oaxaca decomposition), thus reinforcing the common sense there is a wage differential between formal and informal workers, even when controlling for the productive features of each group.